The Metaphysics of Virtual Space: A Phenomenological Study of Subjectivity and Self-Existence in a Mixed Reality Environment - Satrio Rafli Firmansah (PT. Publikasiku Academic Solution, 2025)
The development of mixed reality technology has given birth to virtual spaces that not only serve as a medium of interaction, but also as an arena for the formation of human existence and subjectivity. This article aims to explore the existential experiences of individuals in virtual spaces through a phenomenological approach. The study was conducted qualitatively on five participants who actively used VR/AR technology, with in-depth interview techniques and participatory observation. The results show that virtual spaces create experiences of self-transcendence, redefinition of the physical body, and fluid identity narratives. These findings indicate that virtual space is a new ontological field that shapes the meaning of human existence beyond the boundaries of the physical world. The practical implications lie in the importance of developing digital technologies that are more reflective and humanistic. This research also opens up space for the development of existence theories in the digital context and enriches interdisciplinary studies between philosophy and technology.